Phonon Kinetics of Fructose at the Melting Transition - A. Davie; F. Vandrevala; S. Dampf; Y. Deng; D. K. George; E. D. Sylvester; T. Korter; E. Einarsson; J. B. Benedict; A. G. Markelz (J. Phys. Chem. C, 2021)
Terahertz time domain spectroscopy (THz TDS) is used to measure the melting kinetics of fructose molecular crystals. Combining single-crystal anisotropy measurements with density functional calculations, we assign the phonon frequencies and interrogate how specific phonons behave with melting. While nearly all the low-frequency phonons continuously red-shift with heating and melting, the lowest-energy phonon polarized along the c-axis blue-shifts at the melting temperature, suggesting an initial structural change immediately before melting. We find that the kinetics follow a 3D growth model with large activation energies, consistent with previous differential scanning calorimetry (DSC) measurements. The large activation energies indicate that multiple H-bonds must break collectively for the transition. The results suggest the generality of the kinetics for molecular crystals and that THz TDS with picosecond resolution could be used to measure ultrafast kinetics.

Blue Shift of a Molecular Crystal Phonon at the Solid to Liquid Phase Transition - Davie, Alex; Vandrevala, Farah; Deng, Yanting; George, D.; Sylvester, Eric D.; Korter, T.; Einarsson, E.; Benedict, Jason B.; Markelz, Andrea (Bulletin of the American Physical Society, 2019)

Tunable Compact Narrow Band THz Sources for Frequency Domain THz Anisotropic Spectroscopy - George, D. K.; LaFave, T. J.; Markelz, A. G.; McNee, I.; Tekavec, P.; Kozlov, V.; Schunemann, P. (Conference on Next-Generation Spectroscopic Technologies XII, 2019)
We demonstrate frequency domain THz anisotropy signature detection for protein crystal models using newly developed compact tunable narrow band THz sources based on Orientation Patterned Gallium Phosphide for turn-key spectroscopic systems.
ISI Document Delivery No.: BN5PJ Times Cited: 0 Cited Reference Count: 17 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Chen JY, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2748852 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Lee Y. S., 2006, APPL PHYS LETT, V89 Lee YS, 2000, APPL PHYS LETT, V76, P2505, DOI 10.1063/1.126390 Lin A., 2013, ANTIPHASE DOMAIN ANN Niessen K. A., BIOPHYSICAL J, V112, P933 Niessen KA, 2019, NAT COMMUN, V10, DOI 10.1038/s41467-019-08926-3 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 PARSONS DF, 1971, APPL OPTICS, V10, P1683 Singh R., 2013, PHYSICS Strachan CJ, 2005, J PHARM SCI-US, V94, P837, DOI 10.1002/jps.20281 Tassev V., 2013, SPIE LASE, V9 Tekavec P., 2017, FRONTIERS OPTICS 201 Tonouchi M, 2007, NAT PHOTONICS, V1, P97, DOI 10.1038/nphoton.2007.3 Walther M, 2003, CHEM PHYS, V288, P261, DOI 10.1016/S0301-0104(03)00031-4 Zeitler JA, 2009, EUR J PHARM BIOPHARM, V71, P2, DOI 10.1016/j.ejpb.2008.08.012 George, D. K. LaFave, T. J. Markelz, A. G. Mcnee, Ian Tekavec, Patrick Kozlov, Vladimir Schunemann, Peter LaFave, Tim/0000-0003-2925-8657 NATIONAL INSTITUTE OF GENERAL MEDICAL SCIENCESUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R41GM125486] Funding Source: NIH RePORTER; NIGMS NIH HHSUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R41 GM125486] Funding Source: Medline 0277-786x 1098311
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation

Increase in Dynamical Collectivity and Directionality of Orange Carotenoid Protein in the Photo-Protective State - Deng, Y. T.; Luck, C. H.; Romo, T. D.; Grossfield, A. M.; Bandara, S.; Ren, Z.; Yang, X. J.; Markelz, A. G. (Biophysical Journal, 2018)
ISI Document Delivery No.: GD5RB Times Cited: 1 Cited Reference Count: 0 Deng, Yanting Luck, Catherine H. Romo, Tod D. Grossfield, Alan M. Bandara, Sepalika Ren, Zhong Yang, Xiaojing Markelz, Andrea G. 62nd Annual Meeting of the Biophysical-Society Feb 17-21, 2018 San Francisco, CA Biophys Soc 1 7 Cell press Cambridge 1542-0086
Keywords: Biophysics

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
ISI Document Delivery No.: EI0HL Times Cited: 541 Cited Reference Count: 209 Cited References: Adam AJL, 2011, J INFRARED MILLIM TE, V32, P976, DOI 10.1007/s10762-011-9809-2 Ahmed SS, 2012, IEEE MICROW MAG, V13, P26, DOI 10.1109/MMM.2012.2205772 Alliance N., 2015, CISC VIS NETW IND GL, P1 [Anonymous], 2013, 178512012 IEEE [Anonymous], 2014, IEEE T ELECT DEVICES, V61 [Anonymous], 2012, 178522016 IEEE [Anonymous], 2015, P17852 IEEE Appleby R, 2015, P SOC PHOTO-OPT INS, V9462 Arnone DD, 1999, PROC SPIE, V3828, P209, DOI 10.1117/12.361037 Ashworth PC, 2009, OPT EXPRESS, V17, P12444, DOI 10.1364/OE.17.012444 AUSTON DH, 1988, IEEE J QUANTUM ELECT, V24, P184, DOI 10.1109/3.114 Barbieri S, 2011, NAT PHOTONICS, V5, P306, DOI [10.1038/NPHOTON.2011.49, 10.1038/nphoton.2011.49] Barker RJ., 2005, MODERN MICROWAVE MIL Basov DN, 2011, REV MOD PHYS, V83, P471, DOI 10.1103/RevModPhys.83.471 Bauwens M. F., 2014, P IEEEMTT S INT MICR, P1, DOI [10.1109/MWSYM.2014.68486 07, DOI 10.1109/MWSYM.2014.6848607] Beard MC, 2002, NANO LETT, V2, P983, DOI 10.1021/nl0256210 Beard MC, 2000, PHYS REV B, V62, P15764, DOI 10.1103/PhysRevB.62.15764 Bechtel HA, 2014, P NATL ACAD SCI USA, V111, P7191, DOI 10.1073/pnas.1400502111 Belkin MA, 2008, OPT EXPRESS, V16, P3242, DOI 10.1364/OE.16.003242 Belkin MA, 2015, PHYS SCRIPTA, V90, DOI 10.1088/0031-8949/90/11/118002 Bell R., 2012, INTRO FOURIER TRANSF Berry CW, 2013, NAT COMMUN, V4, DOI 10.1038/ncomms2638 Blanchard F, 2011, OPT EXPRESS, V19, P8277, DOI 10.1364/OE.19.008277 Blau J, 2013, P FREE EL LAS FEL 20, P486 Booske JH, 2011, IEEE T THZ SCI TECHN, V1, P54, DOI 10.1109/TTHZ.2011.2151610 Booske JH, 2008, PHYS PLASMAS, V15, DOI 10.1063/1.2838240 Boppel S, 2012, 2012 IEEE 12TH TOPICAL MEETING ON SILICON MONOLITHIC INTEGRATED CIRCUITS IN RF SYSTEMS (SIRF), P77, DOI 10.1109/SiRF.2012.6160142 Burghoff D, 2014, NAT PHOTONICS, V8, P462, DOI 10.1038/nphoton.2014.85 Busch SF, 2014, J INFRARED MILLIM TE, V35, P993, DOI 10.1007/s10762-014-0113-9 Byrne MB, 2011, APPL PHYS LETT, V98, DOI 10.1063/1.3579258 Carr GL, 2002, NATURE, V420, P153, DOI 10.1038/nature01175 Carranza IE, 2015, IEEE T THZ SCI TECHN, V5, P892, DOI 10.1109/TTHZ.2015.2463673 Castro-Camus E, 2007, OPT EXPRESS, V15, P7047, DOI 10.1364/OE.15.007047 Chan WL, 2007, REP PROG PHYS, V70, P1325, DOI 10.1088/0034-4885/70/8/R02 Chattopadhyay G, 2011, IEEE T THZ SCI TECHN, V1, P33, DOI 10.1109/TTHZ.2011.2159561 Chen HT, 2003, APPL PHYS LETT, V83, P3009, DOI 10.1063/1.1616668 Chen JN, 2012, NATURE, V487, P77, DOI 10.1038/nature11254 Cocker T L, 2016, J PHYS D, V16, P1421 Cocker TL, 2013, NAT PHOTONICS, V7, P620, DOI [10.1038/NPHOTON.2013.151, 10.1038/nphoton.2013.151] Coleman B, 2001, Issue Brief (Public Policy Inst (Am Assoc Retired Pers)), P1 Cooper KB, 2014, IEEE MICROW MAG, V15, P51, DOI 10.1109/MMM.2014.2356092 Cruz F C, 2007, C MICR OPT Cunningham J, 2010, ELECTRON LETT, V46, pS34, DOI 10.1049/el.2010.3317 Dean P, 2011, OPT LETT, V36, P2587, DOI 10.1364/OL.36.002587 Dietz RJB, 2014, OPT LETT, V39, P6482, DOI 10.1364/OL.39.006482 Dietz RJB, 2014, OPT EXPRESS, V22, P19411, DOI 10.1364/OE.22.019411 Dobrovolsky V, 2007, SEMICOND SCI TECH, V22, P103, DOI 10.1088/0268-1242/22/2/017 Ducournau G, 2014, IEEE T THZ SCI TECHN, V4, P328, DOI 10.1109/TTHZ.2014.2309006 Dunsmore J.P., 2012, HDB MICROWAVE COMPON Duvillaret L, 1999, APPL OPTICS, V38, P409, DOI 10.1364/AO.38.000409 Eisele M, 2014, NAT PHOTONICS, V8, P841, DOI [10.1038/nphoton.2014.225, 10.1038/NPHOTON.2014.225] Falconer RJ, 2012, J INFRARED MILLIM TE, V33, P973, DOI 10.1007/s10762-012-9915-9 Fathololoumi S, 2012, OPT EXPRESS, V20, P3866, DOI 10.1364/OE.20.003866 Fausti D, 2011, SCIENCE, V331, P189, DOI 10.1126/science.1197294 Federici J, 2010, J APPL PHYS, V107, DOI 10.1063/1.3386413 Fei Z, 2012, NATURE, V487, P82, DOI 10.1038/nature11253 FETTERMAN HR, 1974, APPL PHYS LETT, V24, P70, DOI 10.1063/1.1655098 Freeman JR, 2013, OPT EXPRESS, V21, P16162, DOI 10.1364/OE.21.016162 Frisk U, 2003, ASTRON ASTROPHYS, V402, pL27, DOI 10.1051/0004-6361:20030335 Garet F, 2014, APPL PHYS LETT, V105, DOI 10.1063/1.4890732 Gavrilov NG, 2007, NUCL INSTRUM METH A, V575, P54, DOI 10.1016/j.nima.2007.01.023 Gensch M., 2013, P 35 INT FREE EL LAS, P474 George DK, 2012, J OPT SOC AM B, V29, P1406, DOI 10.1364/JOSAB.29.001406 Giliberti V, 2013, APPL PHYS LETT, V103, DOI 10.1063/1.4819734 Grant J, 2013, LASER PHOTONICS REV, V7, P1043, DOI 10.1002/lpor.201300087 Green B, 2016, SCI REP-UK, V6, DOI 10.1038/srep22256 Griffith P.R., 2007, FOURIER TRANSFORM IN GRISCHKOWSKY D, 1990, J OPT SOC AM B, V7, P2006, DOI 10.1364/JOSAB.7.002006 Gruene P, 2008, SCIENCE, V321, P674, DOI 10.1126/science.1161166 Han NR, 2014, OPT LETT, V39, P3480, DOI 10.1364/OL.39.003480 Han RN, 2013, IEEE J SOLID-ST CIRC, V48, P2296, DOI 10.1109/JSSC.2013.2269856 Hanham SM, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4927242 Hassel J, 2015, PROC SPIE, V9651, DOI 10.1117/12.2197522 Hauri CP, 2011, APPL PHYS LETT, V99, DOI 10.1063/1.3655331 He W, 2015, APPL PHYS LETT, V107, DOI 10.1063/1.4932099 Hebling J, 2002, OPT EXPRESS, V10, P1161, DOI 10.1364/OE.10.001161 Heinz E, 2015, J INFRARED MILLIM TE, V36, P879, DOI 10.1007/s10762-015-0170-8 Henry SC, 2012, OPT ENG, V51, DOI 10.1117/1.OE.51.9.091603 Hesler J L, 2006, P 7 INT S SPAC TER T, P215 Hintzsche H, 2012, CRIT REV ENV SCI TEC, V42, P2408, DOI 10.1080/10643389.2011.574206 Hishida M, 2011, PHYS REV LETT, V106, DOI 10.1103/PhysRevLett.106.158102 Ho IC, 2010, OPT EXPRESS, V18, P2872, DOI 10.1364/OE.18.002872 HU BB, 1995, OPT LETT, V20, P1716, DOI 10.1364/OL.20.001716 Huang C, 2012, PHYS REV B, V85 Huber R, 2001, NATURE, V414, P286, DOI 10.1038/35104522 Jankowiak A., 2013, Synchrotron Radiation News, V26, P22, DOI 10.1080/08940886.2013.791212 Jepsen PU, 2007, CHEM PHYS LETT, V442, P275, DOI 10.1016/j.cplett.2007.05.112 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Jepsen PU, 2005, OPT LETT, V30, P29, DOI 10.1364/OL.30.000029 JUICE-Jupiter Icy Moons Explorer, 2014, SRE20141 JUICE EUR S, P1 Kallfass I, 2011, IEEE T THZ SCI TECHN, V1, P477, DOI 10.1109/TTHZ.2011.2160021 Kampfrath T, 2013, NAT PHOTONICS, V7, P680, DOI [10.1038/nphoton.2013.184, 10.1038/NPHOTON.2013.184] Kan T, 2015, NAT COMMUN, V6, DOI 10.1038/ncomms9422 Karpowicz N, 2008, APPL PHYS LETT, V92, DOI 10.1063/1.2828709 Kehr SC, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.256403 Kemp MC, 2011, IEEE T THZ SCI TECHN, V1, P282, DOI 10.1109/TTHZ.2011.2159647 Khalid A, 2014, J APPL PHYS, V115, DOI 10.1063/1.4868705 Kirley MP, 2015, IEEE T THZ SCI TECHN, V5, P1012, DOI 10.1109/TTHZ.2015.2468074 Kiwa T, 2003, OPT LETT, V28, P2058, DOI 10.1364/OL.28.002058 Koch M, 2001, NATO SCI SER II MATH, V27, P241 Koenig S, 2013, NAT PHOTONICS, V7, P977, DOI [10.1038/nphoton.2013.275, 10.1038/NPHOTON.2013.275] Kohler R, 2002, NATURE, V417, P156, DOI 10.1038/417156a Koppens FHL, 2014, NAT NANOTECHNOL, V9, P780, DOI [10.1038/nnano.2014.215, 10.1038/NNANO.2014.215] Kosarev A, 2010, SOLID STATE ELECTRON, V54, P417, DOI 10.1016/j.sse.2009.12.032 Kundu I, 2014, OPT EXPRESS, V22, P16595, DOI 10.1364/OE.22.016595 Kuznetsov SA, 2010, KEY ENG MATER, V437, P276, DOI 10.4028/www.scientific.net/KEM.437.276 Langevin Y, 2005, PAYLOAD MISSION DEFI LaRue JL, 2015, PHYS REV LETT, V115, DOI 10.1103/PhysRevLett.115.036103 Leitenstorfer A, 2014, NEW J PHYS, V16, DOI 10.1088/1367-2630/16/4/045016 Leitner DM, 2006, INT REV PHYS CHEM, V25, P553, DOI 10.1080/01442350600862117 Li LH, 2014, ELECTRON LETT, V50, P309, DOI 10.1049/el.2013.4035 Liu L, 2010, IEEE MICROW WIREL CO, V20, P504, DOI 10.1109/LMWC.2010.2055553 Liu SC, 2016, OPT EXPRESS, V24, P2728, DOI 10.1364/OE.24.002728 Lu X H, 2008, P SOC PHOTO-OPT INS, V7277 Luukanen A, 2003, APPL PHYS LETT, V82, P3970, DOI 10.1063/1.1579562 Mann C, 2009, P SOC PHOTO-OPT INS, V7311, P3970 Mickan S, 2004, PROC SPIE, V5277, P54, DOI 10.1117/12.530386 Mineo M, 2010, IEEE T ELECTRON DEV, V57, P3169, DOI 10.1109/TED.2010.2071876 Mittleman DM, 1996, IEEE J SEL TOP QUANT, V2, P679, DOI 10.1109/2944.571768 Mittleman DM, 1999, APPL PHYS B-LASERS O, V68, P1085, DOI 10.1007/s003400050750 Moon K, 2012, APPL PHYS LETT, V101, DOI 10.1063/1.4733475 Muller AS, 2010, REV ACCEL SCI TECH, V3, P165, DOI 10.1142/S1793626810000427 Muller R, 2015, J INFRARED MILLIM TE, V36, P654, DOI 10.1007/s10762-015-0163-7 Naftaly M, 2015, TERAHERTZ METROLOGY, P1 Nagai M, 2015, OPT EXPRESS, V23, P4641, DOI 10.1364/OE.23.004641 Nagatsuma T, 2012, OPT EXPRESS, V21, P477 Nagel M, 2002, APPL PHYS LETT, V80, P154, DOI 10.1063/1.1428619 Navarro-Cia M, 2015, J INFRARED MILLIM TE, V36, P542, DOI 10.1007/s10762-015-0157-5 Nielsen K, 2009, OPT EXPRESS, V17, P8592, DOI 10.1364/OE.17.008592 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 Nordquist CD, 2011, IEEE J SEL TOP QUANT, V17, P130, DOI 10.1109/JSTQE.2010.2049095 Oh SJ, 2012, J INFRARED MILLIM TE, V33, P74, DOI 10.1007/s10762-011-9847-9 Ojefors E, 2009, IEEE J SOLID-ST CIRC, V44, P1968, DOI 10.1109/JSSC.2009.2021911 Ortolani M, 2008, PHYS REV LETT, V97 Ozerov M, 2014, PHYS REV LETT, V113, DOI 10.1103/PhysRevLett.113.157205 Paoloni C, 2013, IEEE T ELECTRON DEV, V60, P1236, DOI 10.1109/TED.2013.2240686 Parrott EPJ, 2015, APPL SPECTROSC, V69, P1, DOI 10.1366/14-07707 Patrashin M, 2015, IEEE T ELECTRON DEV, V62, P1068, DOI 10.1109/TED.2015.2393358 Peiponen K. E., 2013, TERAHERTZ SPECTROSCO, V171 Peng K, 2015, NANO LETT, V15, P206, DOI 10.1021/nl5033843 Pickwell E, 2004, APPL PHYS LETT, V84, P2190, DOI 10.1063/1.1688448 Ponnampalam L, 2011, J LIGHTWAVE TECHNOL, V29, P2229, DOI 10.1109/JLT.2011.2158186 Pupeza I, 2007, OPT EXPRESS, V15, P4335, DOI 10.1364/OE.15.004335 Rauter P, 2015, LASER PHOTONICS REV, V9, P452, DOI 10.1002/lpor.201500095 Reid CB, 2011, PHYS MED BIOL, V56, P4333, DOI 10.1088/0031-9155/56/14/008 Reid J R, 2012, IEEE 12 TOP M SIL MO, P17 Rosch M, 2015, NAT PHOTONICS, V9, P42, DOI [10.1038/nphoton.2014.279, 10.1038/NPHOTON.2014.279] Rudd JV, 2000, PROC SPIE, V3934, P27, DOI 10.1117/12.386344 Rymanov V, 2015, PHOTONICS, V2, DOI 10.3390/photonics2041152 SANTOS Daisy Conceicao, 2014, THESIS Scherger B, 2011, APPL OPTICS, V50, P2256, DOI 10.1364/AO.50.002256 Schleicher JM, 2009, J APPL PHYS, V105, DOI 10.1063/1.3133093 Schumann S, 2012, OPT EXPRESS, V20, P19200, DOI 10.1364/OE.20.019200 Seeds AJ, 2015, J LIGHTWAVE TECHNOL, V33, P579, DOI 10.1109/JLT.2014.2355137 Sell A, 2008, OPT LETT, V33, P2767, DOI 10.1364/OL.33.002767 Shams H, 2015, IEEE PHOTONICS J, V7, DOI 10.1109/JPHOT.2015.2438437 Shams H, 2014, OPT EXPRESS, V22, P23465, DOI 10.1364/OE.22.023465 Shen YC, 2004, APPL PHYS LETT, V85, P164, DOI 10.1063/1.1768313 Simoens F., 2014, PHILOS T A, V372, P1 Simoens F, 2011, 36 INT C INFR MILL T, P1 Singh A, 2015, OPT EXPRESS, V23, P6656, DOI 10.1364/OE.23.006656 Sirtori C, 2013, NAT PHOTONICS, V7, P691, DOI [10.1038/NPHOTON.2013.208, 10.1038/nphoton.2013.208] SMITH PR, 1988, IEEE J QUANTUM ELECT, V24, P255, DOI 10.1109/3.121 Son JH, 2013, NANOTECHNOLOGY, V24, DOI 10.1088/0957-4484/24/21/214001 Swinyard B, 2013, SPIE SENSORS SYSTEMS Sy S, 2010, PHYS MED BIOL, V55, P7587, DOI 10.1088/0031-9155/55/24/013 Taylor ZD, 2015, IEEE T THZ SCI TECHN, V5, P184, DOI 10.1109/TTHZ.2015.2392628 Teppati V, 2013, CAMB RF MICROW ENG, P1, DOI 10.1017/CBO9781139567626 Tewari P, 2012, P SPIE, V8261 Thomas B., 2014, P 39 INT C INFR MILL, P1 Thumm M, 2014, KIT SCI REPORTS, V7693 Tonouchi M, 2007, NAT PHOTONICS, V1, P97, DOI 10.1038/nphoton.2007.3 Truong BCQ, 2015, IEEE T BIO-MED ENG, V62, P699, DOI 10.1109/TBME.2014.2364025 Turcinkova D, 2015, APPL PHYS LETT, V106, DOI 10.1063/1.4916653 Turner GM, 2002, J PHYS CHEM B, V106, P11716, DOI 10.1021/jp025844e van der Valk NCJ, 2002, APPL PHYS LETT, V81, P1558, DOI 10.1063/1.1503404 van Dijk F, 2014, IEEE PHOTONIC TECH L, V26, P965, DOI 10.1109/LPT.2014.2309353 Vicario C, 2014, PHYS REV LETT, V112, DOI 10.1103/PhysRevLett.112.213901 Vinh NQ, 2015, J CHEM PHYS, V142, DOI 10.1063/1.4918708 Vitiello MS, 2012, NAT PHOTONICS, V6, P525, DOI 10.1038/nphoton.2012.145 Vitiello MS, 2015, OPT EXPRESS, V23, P5167, DOI 10.1364/OE.23.005167 Vitiello MS, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms6884 Wade A, 2009, NAT PHOTONICS, V3, P41, DOI 10.1038/NPHOTON.2008.251 Wallace B., 2015, SPIE NEWSROOM, DOI [10.1117/2.1201503.005871, DOI 10.1117/2.1201503.005871] Wallace VP, 2004, BRIT J DERMATOL, V151, P424, DOI 10.1111/j.1365-2133.2004.06129.x Wang FH, 2015, OPTICA, V2, P944, DOI 10.1364/OPTICA.2.000944 Weightman P, 2012, PHYS BIOL, V9, DOI 10.1088/1478-3975/9/5/053001 Wienold M, 2014, OPT EXPRESS, V22, P3334, DOI 10.1364/OE.22.003334 Wilk R, 2007, C LAS EL BALT MD Williams BS, 2006, ELECTRON LETT, V42, P89, DOI 10.1049/el:20063921 Williams GP, 2006, REP PROG PHYS, V69, P301, DOI 10.1088/0034-4885/69/2/R01 Williams GP, 2008, NAT PHYS, V4, P356, DOI 10.1038/nphys958 Williams MRC, 2013, J PHYS CHEM B, V117, P10444, DOI 10.1021/jp406730a Williams R, 2013, PHYS MED BIOL, V58, P373, DOI 10.1088/0031-9155/58/2/373 Withayachumnankul W, 2008, J OPT SOC AM B, V25, P1059, DOI 10.1364/JOSAB.25.001059 Woerner M, 2013, NEW J PHYS, V15, DOI 10.1088/1367-2630/15/2/025039 Woodward RM, 2003, J INVEST DERMATOL, V120, P72, DOI 10.1046/j.1523-1747.2003.12013.x Wu X, OPT LETT, V39, P5403 Wu ZR, 2013, REV SCI INSTRUM, V84, DOI 10.1063/1.4790427 Xu J, 2003, PROC SPIE, V5268, P19, DOI 10.1117/12.518533 Yamashita M, 2011, OPT EXPRESS, V19, P10864, DOI 10.1364/OE.19.010864 Yan F, 2013, J INFRARED MILLIM TE, V34, P489, DOI 10.1007/s10762-013-0005-4 Yang SH, 2014, IEEE T THZ SCI TECHN, V4, P575, DOI 10.1109/TTHZ.2014.2342505 Yeh KL, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2734374 Zamora A, 2015, IEEE MTT S INT MICR Zhao JF, 2011, IEEE T ELECTRON DEV, V58, P1221, DOI 10.1109/TED.2011.2109723 Zheludev NI, 2012, NAT MATER, V11, P917, DOI [10.1038/NMAT3431, 10.1038/nmat3431] Zhou Y, 2010, PROG ELECTROMAGN RES, V105, P71, DOI 10.2528/PIER10041806 Zibik EA, 2009, NAT MATER, V8, P803, DOI [10.1038/nmat2511, 10.1038/NMAT2511] Dhillon, S. S. Vitiello, M. S. Linfield, E. H. Davies, A. G. Hoffmann, Matthias C. Booske, John Paoloni, Claudio Gensch, M. Weightman, P. Williams, G. P. Castro-Camus, E. Cumming, D. R. S. Simoens, F. Escorcia-Carranza, I. Grant, J. Lucyszyn, Stepan Kuwata-Gonokami, Makoto Konishi, Kuniaki Koch, Martin Schmuttenmaer, Charles A. Cocker, Tyler L. Huber, Rupert Markelz, A. G. Taylor, Z. D. Wallace, Vincent P. Zeitler, J. Axel Sibik, Juraj Korter, Timothy M. Ellison, B. Rea, S. Goldsmith, P. Cooper, Ken B. Appleby, Roger Pardo, D. Huggard, P. G. Krozer, V. Shams, Haymen Fice, Martyn Renaud, Cyril Seeds, Alwyn Stoehr, Andreas Naftaly, Mira Ridler, Nick Clarke, Roland Cunningham, John E. Johnston, Michael B. Huggard, Peter/U-2150-2019; Konishi, Kuniaki/AAN-3624-2020; Zeitler, J. Axel/B-4885-2008; Paoloni, Claudio/AAH-9824-2019; Hoffmann, Matthias C./N-1082-2019; Wallace, Vincent P/A-9320-2012; Johnston, Michael/B-9813-2008; Castro-Camus, Enrique/V-6861-2019; Krozer, Viktor/P-5623-2014; Hoffmann, Matthias C/B-3893-2009; PAOLONI, CLAUDIO/AAA-3211-2020; Gonokami, Makoto/F-3641-2012; Shams, Haymen/H-3754-2012; Ridler, Nick/AAN-9637-2020; Huber, Rupert/N-4126-2018 Konishi, Kuniaki/0000-0003-2389-9787; Zeitler, J. Axel/0000-0002-4958-0582; Hoffmann, Matthias C./0000-0002-3596-9853; Wallace, Vincent P/0000-0003-3814-5400; Johnston, Michael/0000-0002-0301-8033; Krozer, Viktor/0000-0002-2387-1947; Hoffmann, Matthias C/0000-0002-3596-9853; PAOLONI, CLAUDIO/0000-0002-0265-0862; Shams, Haymen/0000-0002-5333-6478; Huber, Rupert/0000-0001-6617-9283; Davies, Alexander/0000-0002-1987-4846; Seeds, Alwyn/0000-0002-5228-627X; Castro-Camus, Enrique/0000-0002-8218-9155; Cunningham, John/0000-0002-1805-9743; Naftaly, Mira/0000-0002-0671-822X; Cumming, David/0000-0002-7838-8362 Engineering and Physical Sciences Research CouncilUK Research & Innovation (UKRI)Engineering & Physical Sciences Research Council (EPSRC) [EP/P015883/1, EP/M00306X/1, EP/K023349/1, EP/M017095/1, EP/L026597/1, EP/J017671/1] Funding Source: researchfish; Natural Environment Research CouncilUK Research & Innovation (UKRI)NERC Natural Environment Research Council [NER/Z/S/2003/00642, NE/L012375/1, NER/Z/S/2000/01292] Funding Source: researchfish; Science and Technology Facilities CouncilUK Research & Innovation (UKRI)Science & Technology Facilities Council (STFC) [ST/P002056/1] Funding Source: researchfish; Direct For Biological SciencesNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Biological InfrastructureNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Molecular and Cellular BioscienceNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1616529] Funding Source: National Science Foundation 566 30 462 Iop publishing ltd Bristol 1361-6463
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Global Picosecond Structural Dynamics of Orange Carotenoid Protein in Photo/Chemical Activated Signaling States - Deng, Y.; Xu, M.; Liu, H.; Blankenship, R.; Markelz, A. (APS 2017 S4.002, 2017)

Orange Carotenoid Protein Picosecond Dynamics Changes with Photo and Chemical Activation - Deng, Y. T.; Xu, M. Y.; Liu, H. J.; Blankenship, R. E.; Markelz, A. G. (Biophysical Journal, 2017)
ISI Document Delivery No.: EW3DS Times Cited: 0 Cited Reference Count: 3 Cited References: King JD, 2014, FEBS LETT, V588, P4561, DOI 10.1016/j.febslet.2014.10.024 Wilson A, 2006, PLANT CELL, V18, P992, DOI 10.1105/tpc.105.040121 Wilson A, 2008, P NATL ACAD SCI USA, V105, P12075, DOI 10.1073/pnas.0804636105 Deng, Yanting Xu, Mengyang Liu, Haijun Blankenship, Robert E. Markelz, Andrea G. 58th Annual Meeting of the Biophysical-Society Feb 15-19, 2014 San Francisco, CA Biophys Soc Liu, Haijun/0000-0003-0537-0302 14 Cell press Cambridge 1542-0086 1
Keywords: Biophysics

Temperature dependence of phonons in photosynthesis proteins - Xu, M.; Myles, D.; Blankenship, R.; Markelz, A. (APS 2017 S4.003, 2017)

Modulated orientation-sensitive terahertz spectroscopy - Singh, R.; George, D. K.; Bae, C. J.; Niessen, K. A.; Markelz, A. G. (Photonics Research, 2016)
Intramolecular vibrations of large macromolecules reside in the terahertz range. In particular, protein vibrations are closely spaced in frequency, resulting in a nearly continuous vibrational density of states. This density of vibrations interferes with the identification of specific absorption lines and their subsequent association with specific functional motions. This challenge is compounded with the absorption being dominated by the solvent and local relaxational motions. A strategy for removing the isotropic relaxational loss and isolating specific vibrations is to use aligned samples and polarization-sensitive measurements. Here, we demonstrate a technique to rapidly attain the anisotropic resonant absorbance using terahertz time domain spectroscopy and a spinning sample. The technique, modulated orientation-sensitive terahertz spectroscopy (MOSTS), has a nonzero signal only for anisotropic samples, as demonstrated by a comparison between a silicon wafer and a wire grid polarizer. For sucrose and oxalic acid molecular crystals, the MOSTS response is in agreement with modeled results for the intermolecular vibrations. Further, we demonstrate that, even in the presence of a large relaxational background, MOSTS isolates underlying vibrational resonances. (C) 2016 Chinese Laser Press
ISI Document Delivery No.: DM9BJ Times Cited: 6 Cited Reference Count: 40 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Aguilar RV, 2012, PHYS REV LETT, V108, DOI 10.1103/PhysRevLett.108.087403 Aschaffenburg DJ, 2012, APPL PHYS LETT, V100, DOI 10.1063/1.4729148 Bahar I, 2005, CURR OPIN STRUC BIOL, V15, P586, DOI 10.1016/j.sbi.2005.08.007 Benkovic SJ, 2003, SCIENCE, V301, P1196, DOI 10.1126/science.1085515 Boehr DD, 2006, CHEM REV, V106, P3055, DOI 10.1021/cr050312q Chen JY, 2005, PHYS REV E, V72, DOI 10.1103/PhysRevE.72.040901 Chen Q, 1999, APPL PHYS LETT, V74, P3435, DOI 10.1063/1.124119 Daniel RM, 2003, ANNU REV BIOPH BIOM, V32, P69, DOI 10.1146/annurev.biophys.32.110601.142445 Diehl M, 1997, BIOPHYS J, V73, P2726, DOI 10.1016/S0006-3495(97)78301-2 Ebbinghaus S, 2007, P NATL ACAD SCI USA, V104, P20749, DOI 10.1073/pnas.0709207104 Falconer RJ, 2012, J INFRARED MILLIM TE, V33, P973, DOI 10.1007/s10762-012-9915-9 Fan ST, 2014, J PHYS D APPL PHYS, V47, DOI 10.1088/0022-3727/47/37/374009 Frauenfelder H, 2006, P NATL ACAD SCI USA, V103, P15469, DOI 10.1073/pnas.0607168103 Gabel F, 2002, Q REV BIOPHYS, V35, P327, DOI 10.1017/S0033583502003840 George DK, 2012, J OPT SOC AM B, V29, P1406, DOI 10.1364/JOSAB.29.001406 Giraud G, 2003, BIOPHYS J, V85, P1903, DOI 10.1016/S0006-3495(03)74618-9 Hammes GG, 2011, BIOCHEMISTRY-US, V50, P10422, DOI 10.1021/bi201486f Jackson J.D., 1975, CLASSICAL ELECTRODYN Jenkins GS, 2010, REV SCI INSTRUM, V81, DOI 10.1063/1.3480554 Jepsen PU, 2007, CHEM PHYS LETT, V442, P275, DOI 10.1016/j.cplett.2007.05.112 Karplus M, 2005, P NATL ACAD SCI USA, V102, P6679, DOI 10.1073/pnas.0408930102 Kim SJ, 2008, ANGEW CHEM INT EDIT, V47, P6486, DOI 10.1002/anie.200802281 Kindt JT, 1996, J PHYS CHEM-US, V100, P10373, DOI 10.1021/jp960141g King MD, 2010, J PHYS CHEM A, V114, P7127, DOI 10.1021/jp101935n Kroll J, 2007, VIB SPECTROSC, V43, P324, DOI 10.1016/j.vibspec.2006.03.010 Leitner DM, 2008, HFSP J, V2, P314, DOI 10.2976/1.2976661 Li M, 2011, OPT LETT, V36, P3633, DOI 10.1364/OL.36.003633 Liu D, 2008, PHYS REV LETT, V101, DOI 10.1103/PhysRevLett.101.135501 Niessen Katherine A, 2015, Biophys Rev, V7, P201, DOI 10.1007/s12551-015-0168-4 PETHIG R, 1995, PROTEIN SOLVENT INTE, P265 Planken PCM, 2001, J OPT SOC AM B, V18, P313, DOI 10.1364/JOSAB.18.000313 Rheinstadter MC, 2009, PHYS REV LETT, V103, DOI 10.1103/PhysRevLett.103.128104 RUPLEY JA, 1991, ADV PROTEIN CHEM, V41, P37 Singh R, 2012, J PHYS CHEM A, V116, P10359, DOI 10.1021/jp307288r TORGESEN JL, 1964, SCIENCE, V146, P53, DOI 10.1126/science.146.3640.53 Vinh NQ, 2011, J AM CHEM SOC, V133, P8942, DOI 10.1021/ja200566u Walther M, 2003, CHEM PHYS, V288, P261, DOI 10.1016/S0301-0104(03)00031-4 Xu J, 2006, J PHYS CHEM B, V110, P24255, DOI 10.1021/jp064830w Yasumatsu N, 2012, REV SCI INSTRUM, V83, DOI 10.1063/1.3683570 Singh, Rohit George, Deepu Koshy Bae, Chejin Niessen, K. A. Markelz, A. G. George, Deepu/J-9882-2014 George, Deepu/0000-0003-0021-0705 National Science Foundation (NSF)National Science Foundation (NSF) [DBI2959989]; University at Buffalo (UB) [1126960-1-68255]; Los Alamos National Laboratory (LANL)United States Department of Energy (DOE)Los Alamos National Laboratory [1125895-1-71842]; Direct For Biological SciencesNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation; Div Of Biological InfrastructureNational Science Foundation (NSF)NSF - Directorate for Biological Sciences (BIO) [1556359] Funding Source: National Science Foundation National Science Foundation (NSF) (DBI2959989); University at Buffalo (UB) (Holm Fund 1126960-1-68255); Los Alamos National Laboratory (LANL) (Molecular Crystal Studies 1125895-1-71842). 6 26 Optical soc amer Washington
Keywords: absorption-spectroscopy; dynamics; enzyme catalysis; low-frequency modes; lysozyme; neutron-scattering; Optics; perspective; polarization modulation; proteins; water

Measuring phonons in protein crystals - Acbas, G.; Niessen, K. A.; George, D. K.; Snell, E.; Markelz, A. G. (Ultrafast Phenomena and Nanophotonics Xvii, 2013)
Using Terahertz near field microscopy we find orientation dependent narrow band absorption features for lysozyme crystals. Here we discuss identification of protein collective modes associated with the observed features. Using normal mode calculations we find good agreement with several of the measured features, suggesting that the modes arise from internal molecular motions and not crystal phonons. Such internal modes have been associated with protein function.
ISI Document Delivery No.: BGG42 Times Cited: 0 Cited Reference Count: 5 Cited References: Bahar I, 2005, CURR OPIN STRUC BIOL, V15, P586, DOI 10.1016/j.sbi.2005.08.007 BROOKS B, 1985, P NATL ACAD SCI USA, V82, P4995, DOI 10.1073/pnas.82.15.4995 BROOKS BR, 1983, J COMPUT CHEM, V4, P187, DOI 10.1002/jcc.540040211 Karplus M, 2005, P NATL ACAD SCI USA, V102, P6679, DOI 10.1073/pnas.0408930102 Planken PCM, 2011, J INFRARED MILLIM TE, V32, P975, DOI 10.1007/s10762-011-9824-3 Acbas, Gheorghe Niessen, Katherine A. George, Deepu K. Snell, Edward Markelz, A. G. Proceedings Paper Conference on Ultrafast Phenomena and Nanophotonics XVII Feb 03-06, 2013 San Francisco, CA SPIE, Femtolasers Inc Snell, Edward/G-2055-2018; George, Deepu/J-9882-2014 Snell, Edward/0000-0001-8714-3191; George, Deepu/0000-0003-0021-0705; Markelz, Andrea/0000-0003-0443-4319 National Science Foundation MRI2 [DBI2959989] We thank the National Science Foundation MRI2 grant DBI2959989 for support. 1000 20th st, po box 10, bellingham, wa 98227-0010 usa 0277-786x 862305
Keywords: correlated motions; dynamics; mode; molecular crystals; molecular vibrations; normal modes; phonons; protein dynamics; spectroscopy; Terahertz

Photoactive yellow protein terahertz response: hydration, heating and intermediate states - George, Deepu K; Knab, Joseph R; He, Yunfen; Kumauchi, Masato; Birge, Robert R; Hoff, Wouter D; Markelz, Andrea G (IEEE Transactions on Terahertz Science and Technology, 2013)

Improved mode assignment for molecular crystals through anisotropic terahertz spectroscopy - Singh, Rohit; George, Deepu Koshy; Benedict, Jason B; Korter, Timothy M; Markelz, Andrea G (The Journal of Physical Chemistry A, 2012)

Terahertz Response and Colossal Kerr Rotation from the Surface States of the Topological Insulator Bi2Se3 - Aguilar, R. V.; Stier, A. V.; Liu, W.; Bilbro, L. S.; George, D. K.; Bansal, N.; Wu, L.; Cerne, J.; Markelz, A. G.; Oh, S.; Armitage, N. P. (Physical Review Letters, 2012)
We report the THz response of thin films of the topological insulator Bi2Se3. At low frequencies, transport is essentially thickness independent showing the dominant contribution of the surface electrons. Despite their extended exposure to ambient conditions, these surfaces exhibit robust properties including narrow, almost thickness-independent Drude peaks, and an unprecedentedly large polarization rotation of linearly polarized light reflected in an applied magnetic field. This Kerr rotation can be as large as 65 degrees and can be explained by a cyclotron resonance effect of the surface states.
ISI Document Delivery No.: 896NY Times Cited: 164 Cited Reference Count: 35 Cited References: Akhmerov AR, 2009, PHYS REV LETT, V102, DOI 10.1103/PhysRevLett.102.216404 Alpichshev Z, 2010, PHYS REV LETT, V104, DOI 10.1103/PhysRevLett.104.016401 Analytis JG, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.205407 Bansal N., ARXIV11045709 Benia HM, 2011, PHYS REV LETT, V107, DOI 10.1103/PhysRevLett.107.177602 Bianchi M, 2010, NAT COMMUN, V1, DOI 10.1038/ncomms1131 Butch NP, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.241301 Chen J, 2011, PHYS REV B, V83, DOI 10.1103/PhysRevB.83.241304 Chen YL, 2009, SCIENCE, V325, P178, DOI 10.1126/science.1173034 Essin AM, 2009, PHYS REV LETT, V102, DOI 10.1103/PhysRevLett.102.146805 Eto K, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.195309 Fu L, 2007, PHYS REV B, V76, DOI 10.1103/PhysRevB.76.045302 Fu L, 2008, PHYS REV LETT, V100, DOI 10.1103/PhysRevLett.100.096407 Hsieh D, 2008, NATURE, V452, P970, DOI 10.1038/nature06843 Hsieh D, 2009, NATURE, V460, P1101, DOI 10.1038/nature08234 Jenkins GS, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.125120 King PDC, 2011, PHYS REV LETT, V107, DOI 10.1103/PhysRevLett.107.096802 LaForge AD, 2010, PHYS REV B, V81, DOI 10.1103/PhysRevB.81.125120 Lan YP, 2011, PHYS REV B, V83, DOI 10.1103/PhysRevB.83.205109 Maciejko J, 2010, PHYS REV LETT, V105, DOI 10.1103/PhysRevLett.105.166803 Moore JE, 2007, PHYS REV B, V75, DOI 10.1103/PhysRevB.75.121306 Qi XL, 2008, PHYS REV B, V78, DOI 10.1103/PhysRevB.78.195424 Qu DX, 2010, SCIENCE, V329, P821, DOI 10.1126/science.1189792 Roushan P, 2009, NATURE, V460, P1106, DOI 10.1038/nature08308 Roy R, 2009, PHYS REV B, V79, DOI 10.1103/PhysRevB.79.195322 Steinberg H, 2011, PHYS REV B, V84, DOI 10.1103/PhysRevB.84.233101 Sushkov AB, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.125110 THOULESS DJ, 1982, PHYS REV LETT, V49, P405, DOI 10.1103/PhysRevLett.49.405 Tkachov G, 2011, PHYS REV B, V84, DOI 10.1103/PhysRevB.84.035405 Tse WK, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.161104 Tse WK, 2010, PHYS REV LETT, V105, DOI 10.1103/PhysRevLett.105.057401 VONKLITZING K, 1980, PHYS REV LETT, V45, P494, DOI 10.1103/physrevlett.45.494 Xia Y, 2009, NAT PHYS, V5, P398, DOI 10.1038/NPHYS1274 Xiong J., PHYSICA A E IN PRESS Zhang XA, 2010, PHYS REV B, V82, DOI 10.1103/PhysRevB.82.245107 Aguilar, R. Valdes Stier, A. V. Liu, W. Bilbro, L. S. George, D. K. Bansal, N. Wu, L. Cerne, J. Markelz, A. G. Oh, S. Armitage, N. P. George, Deepu/J-9882-2014; Aguilar, Rolando Valdes/A-6637-2012; Liu, Wei/H-5999-2012; Wu, Liang/C-8715-2015 George, Deepu/0000-0003-0021-0705; Aguilar, Rolando Valdes/0000-0002-4321-4792; Wu, Liang/0000-0003-1696-7809; Markelz, Andrea/0000-0003-0443-4319 "Institute for Quantum Matter" DOE [DE-FG02-08ER46544]; Gordon and Betty Moore FoundationGordon and Betty Moore Foundation; NSFNational Science Foundation (NSF) [MRI-R2 0959989, DMR-1006078, DMR-0845464]; IAMDN of Rutgers University; ONROffice of Naval Research [N000140910749]; Division Of Materials ResearchNational Science Foundation (NSF)NSF - Directorate for Mathematical & Physical Sciences (MPS) [0845464] Funding Source: National Science Foundation The authors would like to thank H. D. Drew, J. Hancock, Z. Hao, G. S. Jenkins, A. Kuzmenko, A. MacDonald, N. A. Mecholsky, A. J. Pearson, O. Tchernyshyov, W-K. Tse, and Y. Wan for helpful discussions and/or correspondences. Support for the measurements at JHU was provided under the auspices of the "Institute for Quantum Matter" DOE DE-FG02-08ER46544 and the Gordon and Betty Moore Foundation. The work at UB was supported by NSF MRI-R2 0959989 and NSF DMR-1006078. The work at Rutgers was supported by IAMDN of Rutgers University, NSF DMR-0845464 and ONR N000140910749. 166 3 157 Amer physical soc College pk
Keywords: bi2te3; Physics

Terahertz response of quantum point contacts - Song, J. W.; Kabir, N. A.; Kawano, Y.; Ishibashi, K.; Aizin, G. R.; Mourokh, L.; Reno, J. L.; Markelz, A. G.; Bird, J. P. (Applied Physics LettersApplied Physics LettersApplied Physics Letters, 2008)
We measure a clear terahertz response in the low-temperature conductance of a quantum point contact at 1.4 and 2.5 THz. We show that this photoresponse does not arise from a heating effect, but that it is instead excellently described by a classical model of terahertz-induced gate-voltage rectification. This effect is distinct from the rectification mechanisms that have been studied previously, being determined by the phase-dependent interference of the source drain and gate voltage modulations induced by the terahertz field. (C) 2008 American Institute of Physics.
ISI Document Delivery No.: 310KL Times Cited: 25 Cited Reference Count: 21 Cited References: Aizin GR, 2007, APPL PHYS LETT, V91, DOI 10.1063/1.2800369 ARNONE DD, 1995, APPL PHYS LETT, V66, P3149, DOI 10.1063/1.113705 FENG SC, 1993, PHYS REV B, V48, P5354, DOI 10.1103/PhysRevB.48.5354 Hashiba H, 2004, APPL PHYS LETT, V85, P6036, DOI 10.1063/1.1834716 HU Q, 1993, APPL PHYS LETT, V62, P837, DOI 10.1063/1.108567 Hu Q, 1996, SEMICOND SCI TECH, V11, P1888, DOI 10.1088/0268-1242/11/12/021 JANSSEN TJBM, 1994, J PHYS-CONDENS MAT, V6, pL163, DOI 10.1088/0953-8984/6/13/002 Kabir NA, 2006, APPL PHYS LETT, V89, DOI 10.1063/1.2357605 KARADI C, 1994, J OPT SOC AM B, V11, P2566, DOI 10.1364/JOSAB.11.002566 Knap W, 2002, APPL PHYS LETT, V81, P4637, DOI 10.1063/1.1525851 Knap W, 2002, APPL PHYS LETT, V80, P3433, DOI 10.1063/1.1473685 Lee M, 2005, APPL PHYS LETT, V86, DOI 10.1063/1.1851606 MITTLEMAN D, 2002, SPRINGER SERIES OPTI Peralta XG, 2002, APPL PHYS LETT, V81, P1627, DOI 10.1063/1.1497433 Ryzhii V, 2006, JPN J APPL PHYS 2, V45, pL1118, DOI 10.1143/JJAP.45.L1118 Shaner EA, 2007, APPL PHYS LETT, V90, DOI 10.1063/1.2735943 Shaner EA, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2128057 Teppe F, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2005394 VANHOUTEN H, 1992, SEMICONDUCT SEMIMET, P9 WYSS RA, 1993, APPL PHYS LETT, V63, P1522, DOI 10.1063/1.110736 WYSS RA, 1995, APPL PHYS LETT, V66, P1144, DOI 10.1063/1.113840 Song, J. W. Kabir, N. A. Kawano, Y. Ishibashi, K. Aizin, G. R. Mourokh, L. Reno, J. L. Markelz, A. G. Bird, J. P. Ishibashi, Koji/G-7065-2012; Bird, Jonathan P/G-4068-2010 Ishibashi, Koji/0000-0001-8131-9969; Bird, Jonathan P/0000-0002-6966-9007; Markelz, Andrea/0000-0003-0443-4319 27 6 Amer inst physics Melville 1077-3118
Keywords: detector; devices; field-effect transistors; Physics; plasma-waves; radiation; resonant detection; subterahertz; transport

Terahertz spectroscopy of bacteriorhodopsin and rhodopsin: Similarities and differences - Balu, R.; Zhang, H.; Zukowski, E.; Chen, J. Y.; Markelz, A. G.; Gregurick, S. K. (Biophysical Journal, 2008)
We studied the low-frequency terahertz spectroscopy of two photoactive protein systems, rhodopsin and bacteriorhodopsin, as a means to characterize collective low-frequency motions in helical transmembrane proteins. From this work, we found that the nature of the vibrational motions activated by terahertz radiation is surprisingly similar between these two structurally similar proteins. Specifically, at the lowest frequencies probed, the cytoplasmic loop regions of the proteins are highly active; and at the higher terahertz frequencies studied, the extracellular loop regions of the protein systems become vibrationally activated. In the case of bacteriorhodopsin, the calculated terahertz spectra are compared with the experimental terahertz signature. This work illustrates the importance of terahertz spectroscopy to identify vibrational degrees of freedom which correlate to known conformational changes in these proteins.
ISI Document Delivery No.: 280IP Times Cited: 50 Cited Reference Count: 72 Cited References: Abdulaev NG, 1998, P NATL ACAD SCI USA, V95, P12854, DOI 10.1073/pnas.95.22.12854 Alexandrov V, 2005, PROTEIN SCI, V14, P633, DOI 10.1110/ps.04882105 Alexiev U, 2003, J MOL BIOL, V328, P705, DOI 10.1016/S0022-2836(03)00326-7 Altenbach C, 2001, BIOCHEMISTRY-US, V40, P15493, DOI 10.1021/bi011545o AMADEI A, 1993, PROTEINS, V17, P412, DOI 10.1002/prot.340170408 Balog E, 2004, PHYS REV LETT, V93, DOI 10.1103/PhysRevLett.93.028103 Beck M, 1998, BIOCHEMISTRY-US, V37, P7630, DOI 10.1021/bi9801560 Bizzarri AR, 2001, EUR BIOPHYS J BIOPHY, V30, P443, DOI 10.1007/s002490100167 BROOKS B, 1983, P NATL ACAD SCI-BIOL, V80, P6571, DOI 10.1073/pnas.80.21.6571 BROOKS BR, 1995, J COMPUT CHEM, V16, P1522, DOI 10.1002/jcc.540161209 Bu ZM, 2000, J MOL BIOL, V301, P525, DOI 10.1006/jmbi.2000.3978 Chen JY, 2005, PHYS REV E, V72, DOI 10.1103/PhysRevE.72.040901 Chen Q, 2001, J OPT SOC AM B, V18, P823, DOI 10.1364/JOSAB.18.000823 Chung HS, 2005, P NATL ACAD SCI USA, V102, P612, DOI 10.1073/pnas.0408646102 Crozier PS, 2003, J MOL BIOL, V333, P493, DOI 10.1016/j.jmb.2003.08.045 Farrens DL, 1996, SCIENCE, V274, P768, DOI 10.1126/science.274.5288.768 Filippovich S. Y., 2004, PHOTOCHEM PHOTOBIOL, V3, P1 Fotiadis D, 2006, CURR OPIN STRUC BIOL, V16, P252, DOI 10.1016/j.sbi.2006.03.013 Gabel F, 2005, BIOPHYS J, V89, P3303, DOI 10.1529/biophysj.105.061028 Gabel F, 2002, Q REV BIOPHYS, V35, P327, DOI 10.1017/S0033583502003840 Getmanova E, 2004, BIOCHEMISTRY-US, V43, P1126, DOI 10.1021/bi030120u Giraud G, 2003, BIOPHYS J, V85, P1903, DOI 10.1016/S0006-3495(03)74618-9 GRISCHKOWSKY D, 1991, FEMTOSECOND PULSES T Groma GI, 2001, BIOPHYS J, V81, P3432, DOI 10.1016/S0006-3495(01)75975-9 Hendler RW, 2003, EUR J BIOCHEM, V270, P1920, DOI 10.1046/j.1432-1033.2003.03547.x Hu KS, 2000, J PHOTOCH PHOTOBIO B, V58, P163, DOI 10.1016/S1011-1344(00)00125-1 Humphrey W, 1996, J MOL GRAPH MODEL, V14, P33, DOI 10.1016/0263-7855(96)00018-5 ICHIYE T, 1991, PROTEINS, V11, P205, DOI 10.1002/prot.340110305 Jaaskelainen S, 1998, PROTEIN SCI, V7, P1359 Joti Y, 2004, PHYSICA B, V350, pE627, DOI 10.1016/j.physb.2004.03.167 Kamikubo H, 1997, BIOCHEMISTRY-US, V36, P12282, DOI 10.1021/bi9712302 Kataoka M, 2000, BBA-BIOENERGETICS, V1460, P166, DOI 10.1016/S0005-2728(00)00137-7 Keskin O, 2000, BIOPHYS J, V78, P2093, DOI 10.1016/S0006-3495(00)76756-7 Kim JE, 2003, BIOCHEMISTRY-US, V42, P5169, DOI 10.1021/bi030026d Kim JE, 2002, J PHYS CHEM A, V106, P8508, DOI 10.1021/jp021069r Knab J, 2006, BIOPHYS J, V90, P2576, DOI 10.1529/biophysj.105.069088 KONIG B, 1989, P NATL ACAD SCI USA, V86, P6878, DOI 10.1073/pnas.86.18.6878 Korter TM, 2006, CHEM PHYS LETT, V418, P65, DOI 10.1016/j.cplett.2005.10.097 Koutsopoulos S, 2005, PROTEINS, V61, P377, DOI 10.1002/prot.20606 Langen R, 1999, BIOCHEMISTRY-US, V38, P7918, DOI 10.1021/bi990010g Lee AG, 2004, BBA-BIOMEMBRANES, V1666, P62, DOI 10.1016/j.bbamem.2004.05.012 Li J, 2004, J MOL BIOL, V343, P1409, DOI 10.1016/j.jmb.2004.08.090 Liang Y, 2003, J BIOL CHEM, V278, P21655, DOI 10.1074/jbc.M302536200 MacKerell AD, 2001, BIOPOLYMERS, V56, P257 Markelz A, 2002, PHYS MED BIOL, V47, P3797, DOI 10.1088/0031-9155/47/21/318 Markelz AG, 2000, CHEM PHYS LETT, V320, P42, DOI 10.1016/S0009-2614(00)00227-X McCamant DW, 2005, J PHYS CHEM B, V109, P10449, DOI 10.1021/jp050095x Niv MY, 2006, J COMPUT AID MOL DES, V20, P437, DOI 10.1007/s10822-006-9061-3 Oesterhelt D, 1974, Methods Enzymol, V31, P667 Okada T, 2001, CURR OPIN STRUC BIOL, V11, P420, DOI 10.1016/S0959-440X(00)00227-X Pitman MC, 2005, J AM CHEM SOC, V127, P4576, DOI 10.1021/ja042715y Rader AJ, 2004, P NATL ACAD SCI USA, V101, P7246, DOI 10.1073/pnas.0401429101 Ridge KD, 2003, TRENDS BIOCHEM SCI, V28, P479, DOI 10.1016/S0968-0004(03)00172-5 Ruprecht JJ, 2004, EMBO J, V23, P3609, DOI 10.1038/sj.emboj.7600374 Saam J, 2002, BIOPHYS J, V83, P3097, DOI 10.1016/S0006-3495(02)75314-9 Sass HJ, 2000, NATURE, V406, P649, DOI 10.1038/35020607 Schmuttenmaer CA, 2004, CHEM REV, V104, P1759, DOI 10.1021/cr020685g Siegel PH, 2004, IEEE T MICROW THEORY, V52, P2438, DOI 10.1109/TMTT.2004.835916 Siegrist K, 2006, J AM CHEM SOC, V128, P5764, DOI 10.1021/ja058176u Subramaniam S, 2000, BBA-BIOENERGETICS, V1460, P157, DOI 10.1016/S0005-2728(00)00136-5 Tajkhorshid E, 2000, BIOPHYS J, V78, P683, DOI 10.1016/S0006-3495(00)76626-4 Tama F, 2000, PROTEINS, V41, P1 Tama F, 2002, J MOL BIOL, V321, P297, DOI 10.1016/S0022-2836(02)00627-7 Tama F, 2001, PROTEIN ENG, V14, P1, DOI 10.1093/protein/14.1.1 Teller DC, 2001, BIOCHEMISTRY-US, V40, P7761, DOI 10.1021/bi0155091 Thomas A, 1999, PROTEINS, V34, P96, DOI 10.1002/(SICI)1097-0134(19990101)34:1<96::AID-PROT8>3.0.CO;2-0 Ujj L, 1998, BIOPHYS J, V74, P1492, DOI 10.1016/S0006-3495(98)77861-0 Vogel R, 2004, J MOL BIOL, V338, P597, DOI 10.1016/j.jmb.2004.03.006 Vogel R, 2003, BIOPOLYMERS, V72, P133, DOI 10.1002/bip.10407 Whitmire SE, 2003, BIOPHYS J, V85, P1269, DOI 10.1016/S0006-3495(03)74562-7 Yan ECY, 2004, BIOCHEMISTRY-US, V43, P10867, DOI 10.1021/bi0400148 Zhang J, 2006, PROTEIN PEPTIDE LETT, V13, P33, DOI 10.2174/092986606774502027 Balu, R. Zhang, H. Zukowski, E. Chen, J. -Y. Markelz, A. G. Gregurick, S. K. Zhang, Hailiang/F-8325-2010 Markelz, Andrea/0000-0003-0443-4319 52 27 Cell press Cambridge 1542-0086
Keywords: Biophysics; bovine rhodopsin; conformational-changes; elastic; frequency normal-modes; light activation; molecular-dynamics simulation; neutron-scattering; protein-coupled receptors; transmembrane helices; vibrational-modes; wild-type

Terahertz transmission characteristics of high-mobility GaAs and InAs two-dimensional-electron-gas systems - Kabir, N. A.; Yoon, Y.; Knab, J. R.; Chen, J. Y.; Markelz, A. G.; Reno, J. L.; Sadofyev, Y.; Johnson, S.; Zhang, Y. H.; Bird, J. P. (Applied Physics Letters, 2006)
Frequency-dependent complex conductivity of high-mobility GaAs and InAs two-dimensional-electron-gas (2DEG) systems is studied by terahertz time domain spectroscopy. Determining the momentum relaxation time from a Drude model, the authors find a lower value than that from dc measurements, particularly at high frequencies/low temperatures. These deviations are consistent with the ratio tau(t)/tau(q,) where tau(q) is the full scattering time. This suggests that small-angle scattering leads to weaker heating of 2DEGs at low temperatures than expected from dc mobilit9y. (c) 2006 American Institute of Physics.
ISI Document Delivery No.: 089JE Times Cited: 18 Cited Reference Count: 16 Cited References: ANDO T, 1982, REV MOD PHYS, V54, P437, DOI 10.1103/RevModPhys.54.437 ANDO T, 1989, HIGH MAGNETIC FIELDS, V2, P164 Ashcroft NW, 1976, SOLID STATE PHYS, P1 Beard MC, 2000, PHYS REV B, V62, P15764, DOI 10.1103/PhysRevB.62.15764 Cerne J, 2000, PHYS REV B, V61, P8133, DOI 10.1103/PhysRevB.61.8133 COLERIDGE PT, 1991, PHYS REV B, V44, P3793, DOI 10.1103/PhysRevB.44.3793 Dorozhkin PS, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2035883 Knap W, 2002, APPL PHYS LETT, V81, P4637, DOI 10.1063/1.1525851 Knap W, 2002, APPL PHYS LETT, V80, P3433, DOI 10.1063/1.1473685 Kukushkin IV, 2005, APPL PHYS LETT, V86, DOI 10.1063/1.1856143 MADELUNG O, 1996, SEMICONDUCTORS BASIC, P109 MCKNIGHT SW, 1987, INFRARED PHYS, V27, P327, DOI 10.1016/0020-0891(87)90074-1 Peralta XG, 2002, APPL PHYS LETT, V81, P1627, DOI 10.1063/1.1497433 Sadofyev YG, 2002, APPL PHYS LETT, V81, P1833, DOI 10.1063/1.1504882 Shaner EA, 2005, APPL PHYS LETT, V87, DOI 10.1063/1.2128057 ZAWADZKI W, 1974, ADV PHYS, V23, P435, DOI 10.1080/00018737400101371 Kabir, N. A. Yoon, Y. Knab, J. R. Chen, J. -Y. Markelz, A. G. Reno, J. L. Sadofyev, Y. Johnson, S. Zhang, Y. -H. Bird, J. P. Bird, Jonathan P/G-4068-2010 Bird, Jonathan P/0000-0002-6966-9007; Markelz, Andrea/0000-0003-0443-4319 18 15 Amer inst physics Melville
Keywords: field-effect transistors; photoconductivity; Physics; plasma-waves; radiation; resonant detection; subterahertz

Terahertz measurements of the Photoactive Protein Bacteriorhodopsin mutant D96N: M and P states - Chen, C.-Y.; Knab, J. R.; Cerne, J.; Hillebrecht, J. R.; Birge, R. R.; Markelz, A. G. (Mater. Res. Soc. Symp., 2004)
We use terahertz (THz) spectroscopy as a biomaterials characterization tool. Previously we have shown a strong contrast between the THz dielectric response for wild type (WT) and D96N mutant of bacteriorhodopsin. In those studies we observed a large increase in the THz absorbance of WT with excitation to thermally captured photo-intermediates whereas no such increase in absorbance was observed for the mutant D96N. These results suggest that the THz response is sensitive to structural changes and relative flexibility of biomolecules. However the photo-intermediate populations of the WT and D96N samples were not equivalent in those measurements. While the WT samples had relaxed (bR), M and P state intermediates present, the D96N samples had only bR and M states. Here we present terahertz absorbance measurements of D96N as a function of M and P state populations at room temperature. The THz response is constant for intermediate states populations up to 23% M state and up to 30% P state. These results verify that there is a fundamental difference in the conformational dynamics as measured by THz dielectric response for a single residue mutation.

Protein flexibility and conformational state: A comparison of collective vibrational modes of wild-type and D96N bacteriorhodopsin - Whitmire, S. E.; Wolpert, D.; Markelz, A. G.; Hillebrecht, J. R.; Galan, J.; Birge, R. R. (Biophysical Journal, 2003)
Far infrared ( FIR) spectral measurements of wild-type (WT) and D96N mutant bacteriorhodopsin thin films have been carried out using terahertz time domain spectroscopy as a function of hydration, temperature, and conformational state. The results are compared to calculated spectra generated via normal mode analyses using CHARMM. We find that the FIR absorbance is slowly increasing with frequency and without strong narrow features over the range of 2-60 cm(-1) and up to a resolution of 0.17 cm(-1). The broad absorption shifts in frequency with decreasing temperature as expected with a strongly anharmonic potential and in agreement with neutron inelastic scattering results. Decreasing hydration shifts the absorption to higher frequencies, possibly resulting from decreased coupling mediated by the interior water molecules. Ground-state FIR absorbances have nearly identical frequency dependence, with the mutant having less optical density than the WT. In the M state, the FIR absorbance of the WT increases whereas there is no change for D96N. These results represent the first measurement of FIR absorbance change as a function of conformational state.
ISI Document Delivery No.: 705ZZ Times Cited: 117 Cited Reference Count: 55 Cited References: AUSTIN RH, 1975, BIOCHEMISTRY-US, V14, P5355, DOI 10.1021/bi00695a021 Birge RR, 1996, J PHYS CHEM-US, V100, P9990, DOI 10.1021/jp953669e BOUSCHE O, 1992, PHOTOCHEM PHOTOBIOL, V56, P1085, DOI 10.1111/j.1751-1097.1992.tb09732.x BROOKS BR, 1983, J COMPUT CHEM, V4, P187, DOI 10.1002/jcc.540040211 BROOKS BR, 1995, J COMPUT CHEM, V16, P1522, DOI 10.1002/jcc.540161209 Brooks CL, 1988, PROTEINS THEORETICAL Brucherseifer M, 2000, APPL PHYS LETT, V77, P4049, DOI 10.1063/1.1332415 Chen Q, 2001, J OPT SOC AM B, V18, P823, DOI 10.1364/JOSAB.18.000823 DENCHER NA, 1989, P NATL ACAD SCI USA, V86, P7876, DOI 10.1073/pnas.86.20.7876 Der A, 2001, BIOCHEMISTRY-MOSCOW+, V66, P1234, DOI 10.1023/A:1013179101782 Diehl M, 1997, BIOPHYS J, V73, P2726, DOI 10.1016/S0006-3495(97)78301-2 DOSTER W, 1989, NATURE, V337, P754, DOI 10.1038/337754a0 FERRAND M, 1993, P NATL ACAD SCI USA, V90, P9668, DOI 10.1073/pnas.90.20.9668 GENZEL L, 1984, SPECTROSCOPY BIOL MO, P609 GRISCHKOWSKY D, 1991, OSA PROC, V9, P9 Guilbert C, 1996, CHEM PHYS, V204, P327, DOI 10.1016/0301-0104(95)00293-6 Han PY, 2000, OPT LETT, V25, P242, DOI 10.1364/OL.25.000242 Hinsen K, 1998, PROTEINS, V33, P417, DOI 10.1002/(SICI)1097-0134(19981115)33:3<417::AID-PROT10>3.0.CO;2-8 JANEZIC D, 1995, J COMPUT CHEM, V16, P1543, DOI 10.1002/jcc.540161210 Kusnetzow A, 1999, BIOPHYS J, V76, P2370, DOI 10.1016/S0006-3495(99)77394-7 Lanyi JK, 1999, INT REV CYTOL, V187, P161, DOI 10.1016/S0074-7696(08)62418-3 Lanyi JK, 2001, TRENDS BIOTECHNOL, V19, P140, DOI 10.1016/S0167-7799(01)01576-1 LINDSAY SM, 1988, BIOPOLYMERS, V27, P1015, DOI 10.1002/bip.360270610 Lisy V, 1997, J BIOMOL STRUCT DYN, V14, P517, DOI 10.1080/07391102.1997.10508150 LONGBOTTOM C, 2002, POTENTIAL USES TERAH Luecke H, 1999, SCIENCE, V286, P255, DOI 10.1126/science.286.5438.255 Luecke H, 1999, J MOL BIOL, V291, P899, DOI 10.1006/jmbi.1999.3027 MacKerell AD, 1998, J PHYS CHEM B, V102, P3586, DOI 10.1021/jp973084f Markelz AG, 2000, CHEM PHYS LETT, V320, P42, DOI 10.1016/S0009-2614(00)00227-X MCINTOSH AR, 1991, BIOPHYS J, V60, P1, DOI 10.1016/S0006-3495(91)82025-2 MOUAWAD L, 1993, BIOPOLYMERS, V33, P599, DOI 10.1002/bip.360330409 Mouawad L, 1996, J MOL BIOL, V258, P393, DOI 10.1006/jmbi.1996.0257 Nagel M, 2002, APPL PHYS LETT, V80, P154, DOI 10.1063/1.1428619 Oesterhelt D, 1974, Methods Enzymol, V31, P667 Palmo K, 1998, J COMPUT CHEM, V19, P754, DOI 10.1002/(SICI)1096-987X(199805)19:7<754::AID-JCC6>3.0.CO;2-P PERAHIA D, 1995, COMPUT CHEM, V19, P241, DOI 10.1016/0097-8485(95)00011-G Person W.B., 1982, VIBRATIONAL INTENSIT Polavarapu P. L., 1998, VIBRATIONAL SPECTRA POWELL JW, 1991, J MOL STRUCT, V247, P107, DOI 10.1016/0022-2860(91)87067-R POWELL JW, 1987, PHYS REV A, V35, P3929, DOI 10.1103/PhysRevA.35.3929 Ren L, 2001, BIOCHEMISTRY-US, V40, P13906, DOI 10.1021/bi0116487 ROITBERG A, 1995, SCIENCE, V268, P1319, DOI 10.1126/science.7539156 Sass HJ, 1997, EMBO J, V16, P1484, DOI 10.1093/emboj/16.7.1484 Stuart JA, 1996, BIOMEMBR A&B, V2, P33 Urabe H, 1998, BIOPHYS J, V74, P1533, DOI 10.1016/S0006-3495(98)77865-8 VARO G, 1983, BIOPHYS J, V43, P47, DOI 10.1016/S0006-3495(83)84322-7 Walther M, 2000, CHEM PHYS LETT, V332, P389, DOI 10.1016/S0009-2614(00)01271-9 WEIDLICH T, 1990, BIOPOLYMERS, V30, P477, DOI 10.1002/bip.360300324 WEIDLICH T, 1990, J BIOMOL STRUCT DYN, V8, P139, DOI 10.1080/07391102.1990.10507795 WEIDLICH T, 1987, BIOPOLYMERS, V26, P439, DOI 10.1002/bip.360260310 WEIDLICH T, 1988, J PHYS CHEM-US, V92, P6475 WITTLIN A, 1986, PHYS REV A, V34, P493, DOI 10.1103/PhysRevA.34.493 Woolard DL, 1997, J APPL TOXICOL, V17, P243, DOI 10.1002/(SICI)1099-1263(199707)17:4<243::AID-JAT436>3.0.CO;2-6 Xie AH, 2002, PHYS REV LETT, V88, DOI 10.1103/PhysRevLett.88.018102 Zaccai G, 2000, SCIENCE, V288, P1604, DOI 10.1126/science.288.5471.1604 Whitmire, SE Wolpert, D Markelz, AG Hillebrecht, JR Galan, J Birge, RR Markelz, Andrea/0000-0003-0443-4319 NATIONAL INSTITUTE OF GENERAL MEDICAL SCIENCESUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548, R01GM034548] Funding Source: NIH RePORTER; NIGMS NIH HHSUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USANIH National Institute of General Medical Sciences (NIGMS) [R01 GM034548, R01 GM034548-15] Funding Source: Medline 122 3 31 Cell press Cambridge 1542-0086
Keywords: angstrom resolution; Biophysics; dna; films; frequency; harmonic-analysis; inelastic neutron-scattering; large systems; mixed basis; normal-modes; purple membranes; structural-changes; transform infrared-spectroscopy

Terahertz Biosensors based on Xerogel Substrates - Chen, J.-Y.; Cox, W.; Bright, F. V.; Cerne, J.; Markelz, A. G. (Proceedings of the International Symposium on Spectral Sensing Research, 2003)

Ultrafast THz spectroscopy of photoactive biomolecules - Chen, J.-Y.; Whitmire, S. E.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Ultrafast Phenomena in Semiconductors VII, 2003)

THz time domain spectroscopy of biomolecular conformational modes - Markelz, Andrea; Whitmire, Scott; Hillebrecht, Jay; Birge, Robert (Physics in Medicine & Biology, 2002)

Terahertz Time domain spectroscopy of the M intermediate state of Bacteriorhodopsin - Whitmire, S.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Proceedings of the 26th International Conference on Infrared and Millimeter Waves, 2001)

Interband impact ionization by terahertz illumination of InAs heterostructures - Markelz, A. G.; Asmar, N. G.; Brar, B.; Gwinn, E. G. (Applied Physics Letters, 1996)
Experimental studies of InAs heterostructures illuminated by far-infrared (FIR) radiation reveal an abrupt increase in the charge density for FIR intensities above a threshold value that rises with increasing frequency. We attribute this charge density rise to interband impact ionization in a regime in which omega tau(m) similar to 1, where tau(m) is the momentum relaxation time, and f=omega/2 pi is the FIR frequency. The dependence of the density rise on the FIR field strength supports this interpretation, and gives threshold fields of 3.7-8.9 kV/cm for the frequency range 0.3-0.66 THz. (C) 1996 American Institute of Physics.
ISI Document Delivery No.: VY894 Times Cited: 91 Cited Reference Count: 17 Cited References: ASMAR NG, 1995, PHYS REV B, V51, P18041, DOI 10.1103/PhysRevB.51.18041 Asmar NG, 1996, APPL PHYS LETT, V68, P829, DOI 10.1063/1.116547 BAIER HU, 1986, SOLID STATE COMMUN, V58, P327, DOI 10.1016/0038-1098(86)90094-3 BLOEMBER.N, 1974, IEEE J QUANTUM ELECT, VQE10, P375, DOI 10.1109/JQE.1974.1068132 BOLOGNESI CR, 1994, IEEE ELECTR DEVICE L, V15, P16, DOI 10.1109/55.289476 CERNE J, 1995, PHYS REV B, V51, P5253, DOI 10.1103/PhysRevB.51.5253 GANICHEV SD, 1986, ZH EKSP TEOR FIZ+, V90, P445 GAUER C, 1994, SEMICOND SCI TECH, V9, P1580, DOI 10.1088/0268-1242/9/9/002 Kochman B, 1996, APPL PHYS LETT, V68, P1936, DOI 10.1063/1.115631 MARKELZ AG, 1994, SOLID STATE ELECTRON, V37, P1243, DOI 10.1016/0038-1101(94)90399-9 MARKELZ AG, 1994, SEMICOND SCI TECH, V9, P634, DOI 10.1088/0268-1242/9/5S/063 NGUYEN C, 1993, J VAC SCI TECHNOL B, V11, P1706, DOI 10.1116/1.586509 NGUYEN C, 1993, J ELECTRON MATER, V22, P255, DOI 10.1007/BF02665035 TUTTLE G, 1990, J APPL PHYS, V67, P3032, DOI 10.1063/1.345426 Walpole J. N., 1971, Journal of Applied Physics, V42, P5609, DOI 10.1063/1.1659990 WHITE CRH, 1991, APPL PHYS LETT, V58, P1164, DOI 10.1063/1.104352 XIE H, 1994, J APPL PHYS, V76, P92, DOI 10.1063/1.357065 Markelz, AG Asmar, NG Brar, B Gwinn, EG Markelz, Andrea/0000-0003-0443-4319 92 6 Amer inst physics Melville 1077-3118
Keywords: energy; far-infrared excitation; inas/alsb quantum-wells; inplane; modulation; Physics

Third Harmonic Generation in a Gaas/Algaas Superlattice in the Bloch Oscillator Regime - Wanke, M. C.; Markelz, A. G.; Unterrainer, K.; Allen, S. J.; Bhatt, R. (Hot Carriers in Semiconductors, 1996)

QUENCHING OF EXCITONIC QUANTUM-WELL PHOTOLUMINESCENCE BY INTENSE FAR-INFRARED RADIATION - FREE-CARRIER HEATING - Cerne, J.; Markelz, A. G.; Sherwin, M. S.; Allen, S. J.; Sundaram, M.; Gossard, A. C.; Vanson, P. C.; Bimberg, D. (Physical Review B, 1995)
Sherwin, Mark S/Q-4762-2017 Sherwin, Mark S/0000-0002-3869-1893; Markelz, Andrea/0000-0003-0443-4319 29

Third harmonic generation in a GaAs/AlGaAs Superlattice in the Bloch Oscillator Regime - Wanke, M. C.; Markelz, A.G.; Unterrainer, K.; Allen, S. J.; Bhatt, R. (Proceedings of the International Conference on Hot Carriers in Seminconductors, 1995)

Frequency Dependence of the Third Order Susceptibility of InAs Quantum Wells at Terahertz Frequencies - Markelz, A.G.; Cerne, J.; Gwinn, E. G.; Brar, B.; Kroemer, H. (Proceedings of the International Conference on the Physics of Semiconductors, 1994)

Far-infrared nonlinear response of electrons in semiconductor nanostructures - Sherwin, M. S.; Asmar, N. G.; Bewley, W. W.; Craig, K.; Felix, C. L.; Galdrikian, B.; Gwinn, E. G.; Markelz, A.G.; Gossard, A. C.; Hopkins, P. F.; Sundaram, M.; Birnir, B. (SPIE Proceedings, 1993)

Conversion of 124 and 123 + cupric oxide: microstructure and phase diagram - Morris, D. E.; Nickel, J. H.; Markelz, A.G.; Gronksy, R.; Fendorf, M.; Burmester, C. P. (Materials Research Society Symposium Proceedings, 1990)